GE_GERICHTE A/908/2015 vom 18. August 2015 - GE Cour de justice (2015)
PRECPTE; SEQUES; VALIDA; PTEPER | Recours au TF interjeté le 11 mai 2015 par le créancier, rejeté par arrêt du 18 août 2015 ( | LP.88.2; LP.279.1